2019
DOI: 10.1186/s12893-018-0434-z
|View full text |Cite
|
Sign up to set email alerts
|

Stage-related outcome for thymic epithelial tumours

Abstract: Background: Thymic epithelial tumours (TETs) are characterized by a wide variety of biological behaviors. Radical resection and stage are strong prognostic factors. Aim of this study is to review our Single Center Experience. Methods: One hundred and seventy-seven patients observed in the period from January 2000 to December 2016 were included in the study. Data regarding clinicopathologic features, treatment, and survival were collected. Stagerelated clinical standpoints and therapeutic options were also eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…It is well established that surgical resection is the mainstay of thymoma treatment, and can improve survival even in patients with stage IV disease. 15,16 We found that this was reflected in real-world practice, with treatment approaches including surgical resection being the most common for both stage III and IV thymoma in the United States. Surgical resection was often one component of multimodality therapy.…”
Section: Commentmentioning
confidence: 93%
“…It is well established that surgical resection is the mainstay of thymoma treatment, and can improve survival even in patients with stage IV disease. 15,16 We found that this was reflected in real-world practice, with treatment approaches including surgical resection being the most common for both stage III and IV thymoma in the United States. Surgical resection was often one component of multimodality therapy.…”
Section: Commentmentioning
confidence: 93%
“…TET stage is prognostic in both humans and dogs, independent of histologic subtype. 4,19 The most widely used staging system for human TETs, also assessed in dogs, 4 is the Masaoka-Koga system which utilises both surgical and histologic information (Table 2) [20][21][22] although newer tumour, node, metastasis systems may provide more clinically relevant differentiation between stages. 23 Treatment of TETs primarily involves surgical excision.…”
Section: Introductionmentioning
confidence: 99%
“…Given the minimal tumor remnants seen after surgical resection for a Stage 3 thymoma due to its invasion into the surrounding tissue, adjuvant therapy such as radiotherapy or chemotherapy is recommended. If conditions for a possible macroscopically complete resection for a Stage 4 thymoma are not completely achievable, any surgical therapy plan should be avoided due to the fact that extended resections for Stage 3 and 4 thymomas can be technically demanding and have a high associated morbidity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%